The Way of Biology Teachers to Train HOTS to the Students in Online Learning Process - Aulia Hermawati Ulfah; Heri Retnawati; Supahar Supahar (Jurnal Penelitian Pendidikan IPA, 2023)
The implementation of HOTS in the learning process is considered capable of improving the quality of education in Indonesia. However, in online learning conditions, there are many obstacles and limitations to training HOTS in Biology lesson. This study aims to describe biology teachers' knowledge, preparation, and implementation of HOTS training during online learning. This study uses a qualitative approach to the type of phenomenology. This study involved 12 Biology teachers at SMA and SMK in West Java. The data collection technique is carried out through interviews via WhatsApp Call. The data analysis technique used is through reduction, data review, and conclusions drawing. Based on the results of data analysis, it was found that the teacher’s understanding of HOTS learning is still weak, and the implementation of HOTS training during online learning is still not optimal. The most widely used learning model is Problem based Learning. The constraint implementation of online HOTS training is inseparable from the online learning barriers, but teachers also continue to try to handle these barriers with various solutions.